2016
DOI: 10.1007/s00424-016-1830-9
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the activation pathway for TMEM16A chloride channels from macroscopic currents and kinetic models

Abstract: TMEM16A (ANO1), the pore-forming subunit of calcium-activated chloride channels, regulates several physiological and pathophysiological processes such as smooth muscle contraction, cardiac and neuronal excitability, salivary secretion, tumour growth, and cancer progression. Gating of TMEM16A is complex because it involves the interplay between increases in intracellular calcium concentration ([Ca2+]i), membrane depolarization, extracellular Cl− or permeant anions, and intracellular protons. Our goal here was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 53 publications
(136 reference statements)
2
30
0
1
Order By: Relevance
“…; Contreras‐Vite et al . ). Cells were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, 2 m m l ‐glutamine and 1 mg ml −1 Geneticin at 37°C in a 95% O 2 –5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Contreras‐Vite et al . ). Cells were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, 2 m m l ‐glutamine and 1 mg ml −1 Geneticin at 37°C in a 95% O 2 –5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 97%
“…The gating of TMEM16A is a complex process (Contreras‐Vite et al . ). It results from the interaction between the binding of intracellular Ca 2+ , membrane depolarization (Arreola et al .…”
Section: Introductionmentioning
confidence: 97%
“…In addition to its regulation by Ca 2+ , TMEM16A is also regulated by permeant anions that facilitate TMEM16A channel gating (Arreola et al, 1996; Kuruma and Hartzell, 2000; Arreola et al, 2010; Xiao et al, 2011; Terashima et al, 2013; Betto et al, 2014; Contreras-Vite et al, 2016) because ion permeation and gating are coupled (Perez-Cornejo et al, 2004; Betto et al, 2014). Also, protons exert a strong regulatory effect on channel activity.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al () found that replacement of extracellular Cl − with NO 3 − significantly reduced the voltage‐dependent gating of TMEM16A, suggesting the voltage gating of TMEM16A is affected by permeant anions. On the contrary, Contreras‐Vite et al () demonstrated that extracellular Cl − does not alter the apparent Ca 2+ affinity of TMEM16A. Rather, extracellular Cl − can stabilize the open conformation of TMEM16A and contribute to the voltage dependence of activation.…”
Section: Ca2+ and Voltage Dependence Of Tmem16amentioning
confidence: 97%
“…TMEM16A is widely expressed in many cells including epithelia, airway and vascular smooth muscle cells, vascular endothelium, cardiac muscles, olfactory sensory neurons, somatosensory neurons interstitial cells of Cajal (ICC), and nociceptive neurons (K. Ma, Wang, Yu, Wei, & Xiao, ; U. Oh & Jung, ; H. Wang et al, ). The electrophysiological properties of TMEM16A involve calcium and voltage dependence (Contreras‐Vite et al, ; Cruz‐Rangel et al, ; Terashima, Picollo, & Accardi, ; Xiao et al, ), rectifying properties (K. Ma et al, ), ion selectivity (Peters et al, ; Xiao et al, ), activation kinetics (Contreras‐Vite et al, ; Espinosa et al, ), and rundown (Yu, Zhu, Qu, Cui, & Hartzell, ). In addition, the dysfunction of TMEM16A can lead to many diseases, including various cancers (Cao et al, ), gastrointestinal (GI) disorders (Mazzone et al, ), hypertension (Wang, Li, Huai, & Qu, ), and cystic fibrosis (Sondo, Caci, & Galietta, ).…”
Section: Introductionmentioning
confidence: 99%